2017
DOI: 10.1096/fj.201601211r
|View full text |Cite
|
Sign up to set email alerts
|

NFAT5‐sensitive Orai1 expression and store‐operated Ca 2+ entry in megakaryocytes

Abstract: The transcription factor nuclear factor of activated T cells 5 (NFAT5) is up-regulated in several clinical disorders, including dehydration. NFAT5-sensitive genes include serum and glucocorticoid-inducible kinase 1 (SGK1). The kinase is a powerful regulator of Orai1, a Ca channel accomplishing store-operated Ca entry (SOCE). Orai1 is stimulated after intracellular store depletion by the Ca sensors stromal interaction molecule 1 (STIM1), or STIM2, or both. In the present study, we explored whether nuclear facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Even though all CoIP studies presented here are in agreement with the FRET and super resolution results, we would like to highlight the fact that the molecular weight obtained from Orai1 (≈55 kDa) differs from the predicted molecular weight for this protein (≈33 kDa). Thus, we would like to take the CoIP studies with caution, even though other reports have found similar discrepancies in the molecular weight for Orai1 34,35 . Feasible explanations for the higher molecular weight observed may involve glycosylation, phosphorylation, and other post-translational modifications of Orai1 3638 .…”
Section: Discussionmentioning
confidence: 86%
“…Even though all CoIP studies presented here are in agreement with the FRET and super resolution results, we would like to highlight the fact that the molecular weight obtained from Orai1 (≈55 kDa) differs from the predicted molecular weight for this protein (≈33 kDa). Thus, we would like to take the CoIP studies with caution, even though other reports have found similar discrepancies in the molecular weight for Orai1 34,35 . Feasible explanations for the higher molecular weight observed may involve glycosylation, phosphorylation, and other post-translational modifications of Orai1 3638 .…”
Section: Discussionmentioning
confidence: 86%
“…Many immune regulatory molecules and cytokines are also expressed on platelets (eg, Toll‐like receptors, P‐selectin, CD40L, interleukin‐1β, and transforming growth factor‐β) and have the ability to interact with immune cells, with integrin family member playing key roles, 28,29 such as β2 integrin modulating platelet caspase activation and life span in mice 30 . Autoantibody to α v β 3 was detected in immune thrombocytopenia patients and contributes to thrombocytopenia by blocking the adhesion and migration of MKs 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the proteins expressed in megakaryocytes are expected to be transferred into circulating blood platelets 27 . Recent observations revealed a powerful SGK1 dependent stimulation of ORAI1 expression by NFAT5 overexpression in megakaryocytes 28 .…”
mentioning
confidence: 99%